Interactions of exoplanets with their environment - Strugarek, Antoine (Comptes Rendus. Physique, 2023)
Exoplanets on close-in orbit are subject to intense interactions with their host star. They receive a strong irradiation from the star, trigger tides within their host, and stars and close-in planets can be magnetically connected. In this review, I introduce the physical concepts behind these three types of interaction. I provide simple scaling-laws for their relative strengths, and highlight the aspects of the interactions that still elude our understanding. For each interaction, I also review their detectable effects on both specific star-planet systems and on the population of exoplanets as we know it today.